Financial Behavior Mediation Effect On The Influence Of Risk Tolerance And Financial Efficacy On Investment Decisions Of Gen Z In Pontianak City - Muhammad Nur Rizki; Fuad Ramdhan Ryanto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study focuses on obtaining an explanation of the influence between the variables of risk tolerance and financial efficacy on the variable of investment decisions using the mediating role of financial behavior. In conducting observations, the researcher applies an associative quantitative research method. This research applies an object of 200 respondents who are Gen Z investors residing in Pontianak City. The analysis of research data was obtained with purposive sampling and Smart-PLS as an analysis tool. The outcome from the research are, directly, Variable risk tolerance & financial efficacy significantly positively affect the financial behavior variable. Then, Investment Decisions are directly influenced by risk tolerance, financial efficacy, & financial behavior variables. Furthermore, there is a mediating role of financial behavior on impact to financial efficacy towards investment decision, but it cannot mediate the impact given by risk tolerance towards investment decision.